Upaya Meningkatkan Motorik Kasar Anak Usia 5-6 Tahun Melalui Senam Tradisonal - Wikaningtyas, Asih; Basith, Abdul (Sultan Idris Journal of Psychology and Education, 2022)
The development of gross motor skills in children is an important factor in carrying out all life activities because it is closely related to the physical and intellectual condition of children. There are still many children aged 5-6 years who have not been able to complete their activities independently because they often get help from adults. Children aged 5-6 years tend to prefer to sit back and relax while playing with gadgets because they don’t require a lot of energy. This study aims to improve children’s gross motor skills through traditional gymnastic activities using the Classroom Action Research (CAR) method. The data analysis technique used is to collect data, reduce data, present data, and conclude observations. Data collection was carried out by observation, interview, and documentation techniques. The results of observations are described in a narrative description. Indicators of success are shown by the Developing As Expected (BSH) and Very Well Developing (BSB) categories. The results of the research at the end of the remedial activity, which is on the fifth day of cycle 2, show that the gross motor skills of children aged 5-6 years have shown the BSH and BSB categories. This indicates that the gross motor skills of children aged 5-6 years through traditional gymnastic activities have increased optimally.